From early symptoms to EEG silence: tracking the neurodegenerative course of sporadic Creutzfeldt-Jakob disease - He, Yunfang; Qiu, Liangliang (Frontiers in Human Neuroscience, 2025)
BackgroundSporadic Creutzfeldt-Jakob disease (sCJD) is a rapidly progressive and fatal neurodegenerative disorder. Early diagnosis remains challenging due to nonspecific initial symptoms. Although electroencephalography (EEG) is a key diagnostic tool, particularly through the detection of periodic sharp wave complexes (PSWCs), the longitudinal evolution of EEG features and their correlation with clinical and neuroimaging progression are not fully characterized.MethodsThis retrospective cohort study analyzed 37 patients diagnosed with probable and very probable sCJD according to the 2021 Chinese diagnostic guidelines. All patients underwent at least one EEG examination. One representative patient was followed for 23 weeks with serial EEG and MRI studies to document dynamic electrophysiological and structural changes. EEG background activity was graded as mild, moderate, or severe, and PSWCs were identified based on standardized criteria. MRI analyses focused on the spatial and temporal progression of hyperintense lesions on DWI and FLAIR sequences.ResultsAmong the 37 patients, 46% underwent initial EEG within 1 month of symptom onset, and 49% exhibited severe background abnormalities. PSWCs were present in 84% of patients at first EEG, with a high prevalence (82%) even in those examined within 4 weeks of onset. Longitudinal analysis in the index case revealed a progressive EEG deterioration: from slowed and disorganized background rhythms and emerging triphasic waves at 8 weeks, to widespread PSWCs with increasing periodicity (9–16 weeks), and finally to a burst-suppression pattern near electrical silence by week 23. Concurrent MRI showed a parallel expansion of hyperintense lesions from unilateral cortical and basal ganglia regions to bilateral involvement, closely correlated with the EEG progression. Statistical analysis showed no significant correlation between survival time and age, time to first EEG, CSF 14–3-3 protein status, or initial EEG background grade. Furthermore, neither the presence of typical PSWCs nor the severity of background activity was associated with survival outcomes.ConclusionEEG, especially the early and highly prevalent presence of PSWCs, offers high diagnostic value in sCJD but does not serve as prognostic predictors. The close correlation between EEG decline and MRI progression supports multimodal monitoring. Serial EEG should be integrated into sCJD diagnosis and follow-up.